Between Hobbes and Locke - Jacob Donald Chatterjee (Locke Studies, 2019)
This article presents a new understanding of how the context of Restoration debates around toleration, magisterial authority and political obligation impinged upon Locke’s mature thought. It proposes that prominent Anglican clergymen, by utilising Hobbist ideas in their arguments for religious conformity, transformed the debate around toleration. In particular, Samuel Parker’s Discourse of Ecclesiastical Politie’s potent mix of Hobbism, theological moralism and Scholastic natural law led to important nonconformists, such as Owen and Ferguson, reshaping their arguments in response. They were forced to make an argument upon first principles as to precisely why Parker’s naturalistic account of ecclesiastical authority was inadequate to justify their own particular view of religious institutions. Crucially, the specific features of Parker’s argument, led to John Humfrey, a largely overlooked figure, developing a set of ideas that preconfigured Locke’s later thought. This article then highlights Locke’s creative engagement with the ideas of his time, by charting the changes to Locke’s ecclesiology and view of natural law from 1667-1674, alongside the similar conceptual shifts made by Humfrey.